Soft wood grafting of Garcinia xanthochymus (Hook. f.) [Syn. G. tinctoria (Wight)] - Minoo Divakaran, K Jayarajan, B Krishnamoorthy, P A Mathew, J Rema (Journal of Spices and Aromatic Crops, 2006)
Soft wood grafting of Garcinia xanthochymus was standardized on 9 month old rootstocks ofthe same species with 90% success. The grafted plants flowered within 3 years after graftingand set fruits in the fourth year, while seed propagated plants did not flower even 6½years after planting in the field.